Molecular dynamics study of tensile properties of graphene/GaN heterostructures. Issue 1 (1st December 2022) - Liu, Dongjing; Zhu, Jingjie; Zhou, Fu; Zhang, Guoqi; Yang, Daoguo
Abstract: Graphene/GaN nanocomposites have been widely used in high-power and high-frequency optoelectronic devices. At present, the thermal transport characteristics of graphene/gallium nitride heterostructures have been investigated by many scholars, but their mechanical properties have not been systematically studied. In this paper, the effects of graphene layer number, temperature and interfacial structure on the mechanical properties of graphene/GaN heterostructures were investigated by molecular dynamics method. The mechanical properties of materials were analyzed by failure stress, failure strain and Young's modulus. The simulation results show that the heterogeneous structure is very sensitive to temperature. When the temperature is set at 2000K, the Young's modulus of the heterostructure decreases by 25.11% compared with that at 300K, which indicates that the increase of temperature will reduce the mechanical properties of graphene composites, However, when the number of graphene layers increases, the mechanical properties of the heterostructures also improved. With the number of graphene layers is set from 1 layer to 5 layers, the performance of the heterostructure is improved, and its Young's modulus increases by 48.46%. In addition, the effect of interface structure on the young's modulus of the heterostructure structure is not obvious, but it will affect the maximum failure stress and maximum failure strain of the material. The mechanical properties of graphene in cross section contact with gallium atom are better than those of nitrogen atom. It is beneficial to improve the reliability of microelectronic devices to control and design heterogeneous structures based on the research results.